ROLE OF SILICON IN THE PHOSPHORUS NUTRITION AND GROWTH OF THE OATS (AVENA SATIVA L.) AT DIFFERENT PHOSPHORUS LEVELS - R. Bakır; A. Horuz (Journal of Animal and Plant Sciences, 2021)
In some circumstances, silicon (Si) application is environmentally the most useful way of correcting or alleviating the negative effects of some abiotic stress factors on plant growth, e.g., nutrient element deficiency and toxicity. Therefore, the aim of this study was to investigate the effects of Si and phosphorus (P) levels, and their interaction, on the dry weight (DW) biomass and P concentration of 65 days old oats plants (Avena sativa L. cv. Faikbey) in a pot trial. The experiment was conducted with a completely randomized design with full factorial arrangement and three replicates under greenhouse conditions. The factors were Si application rate (0, 50, 100, 200 and 400 mg kg-1 soil) and P level (0, 10, 25, 50, 100 and 250 mg kg-1 soil). Increasing the P level in the soil from 0 mg kg-1 to 100 mg kg-1 significantly increased (P<0.05) the DW of oats shoots from 3.60 g pot-1 to 12.01 g pot-1, respectively, compared to the control, but the DW significantly decreased from 12.01 g pot-1 to 8.68 g pot-1 at 250 mg kg-1 of P, due to P toxicity. In comparison, Si at all application rates significantly increased shoot DW compared to the control. The DW of shoots corresponding to the increasing Si concentrations were 7.06 (control), 7.82, 8.01, 8.55 and 9.08 g pot-1, respectively. The relative DW increases, compared to the control as a function of increasing Si rate, were 10.76, 13.46, 21.10 and 28.61%, for 50, 100, 200 and 400 mg kg-1 of Si, respectively. The lowest shoot P concentration (0.03%) was in the control treatment and the highest was 0.45% at 250 mg P kg- 1 of soil, without Si application. The P concentration was 0.20% at 200 mg Si kg-1, without P application. Furthermore, P concentrations continuously decreased from 0.45 % to 0.29% as Si concentrations increased from 0 to 400 mgSi kg-1 at 250 mg P kg-1. It is concluded that Si application to moderately acidic soils may be an effective method for the reduction of both P deficiency stress and P toxicity in oats, the latter by decreasing excess P absorption.
Keywords: silicon application; phosphorus fertilizer; oat; dry weight; P concentration